The botany of desire : a plant's eye view of the world - Pollan, Michael (Random House, 2001)
"An Idaho farmer cultivates Russet Burbank potatoes so that a customer at a McDonald's half a world away can enjoy a long, golden french fry. A gardener plants tulip bulbs in the fall and, come spring, has a riotous patch of color to admire. Two straightforward examples of how humans act on nature to get what we want. Or are they? What if those potatoes and tulips have evolved to gratify certain human desires so that humans will help them multiply? What if, in other words, these plants are using us just as we use them?".